Ways to organize the activities of a tax inspector attached to a mahallabay in Uzbekistan and improve mahallabay mechanisms - Xudoyberdiev Obiddin Qaxramonovich (Genius Journals, 2025)
This article highlights the role and importance of interregional tax inspection in improving large-scale reforms aimed at creating favorable conditions for conducting business activities in the tax sphere in the country and further strengthening the confidence of business circles. At the same time, some important reforms in the organization of makhallabay work in the tax system of Uzbekistan are studied, foreign experience is studied, scientific and practical conclusions and proposals are developed on its application in our country.
Keywords: Tax policy; makhallabay; enterprise; tax revenues